Perspective of Children with Disabilities as the Implementation of AI in School: Focus Study in Philippines, Malaysia, and Indonesia - Kurnia, Nova; Enanoria, Cristine Joy; Bauzir, Arij Fathir; Basri, Nurul Ain Nabillah Binti; Fauzia, Novia Alifah; Wulandari, Widya; Barrios, Rubylin G; Hendriyana, Hendriyana (International Journal of Ethnoscience and Technology in Education, 2025)
This study explores the perspectives of students with disabilities on the implementation of Artificial Intelligence (AI) in schools across Philippines, Malaysia, and Indonesia. AI is increasingly recognized for its transformative potential in education, particularly in fostering inclusivity through personalized learning, improved accessibility, and enhanced engagement. A qualitative approach, combined with a literature review, was employed to analyze existing research and identify regional differences in AI implementation. Results indicate that AI tools, such as adaptive learning platforms and assistive technologies, significantly benefit students by addressing individual learning needs and overcoming traditional barriers. However, challenges persist, including inadequate infrastructure, insufficient teacher training, and concerns over data privacy and ethical use of sensitive student information. These obstacles are particularly pronounced in rural and underserved areas, highlighting the need for targeted investments and policy reforms. The study recommends prioritizing infrastructure development, implementing comprehensive training programs for educators, and establishing robust ethical frameworks to ensure responsible AI usage. By addressing these challenges and fostering regional collaboration, AI can become a powerful tool for promoting equity and accessibility in education, ultimately enhancing learning outcomes for students with disabilities. Future research should focus on longitudinal studies and firsthand data collection to better understand AI’s long-term impact and refine inclusive educational practices.